Umbilical cord mesenchymal stem cells improve bone regeneration in diabetes mellitus animal model with apical periodontitis - Eric Priyo Prasetyo; Pravinna Saravanan; Deaniddo Kharisna; Christina Immee Wijanarko; Mefina Kuntjoro; Nike Hendrijantini; Evelyn Tjendronegoro (Elsevier, 2025)
Background: Previous studies revealed diabetes mellitus subjects tend to have persistent apical periodontitis. Regenerative stem cells therapy through endodontic procedure is hoped to be a solution. This study assessed bone regeneration in diabetic rats with apical periodontitis through histopathological analysis of osteoblasts and immunohistochemical analysis of runt-related transcription factor 2 (Runx2) and Osterix. Methods: Diabetes mellitus and apical periodontitis was induced on 20 rats. Apical periodontitis was induced on mandibular right first molars under anesthesia. The teeth were left open for 7 days following access cavity and pulp extirpation, then the rats' teeth were endodontically treated and randomly allocated into 4 groups (5 rats per group). The first and second groups was ended at 30 days (C30) and 60 days (C60) and labelled as control. The third and fourth groups was given umbilical cord mesenchymal stem cells and ended at 30 days (T30) and 60 days (T60). The osteoblasts, Runx2 and Osterix were analyzed. ANOVA and Tukey HSD tests were used for analysis. Differences with p values < 0.05 were considered significant. Results: The number of osteoblasts in the apical area in control groups (C30 and C60) and treatment groups (T30 and T60) showed a significant increase (p < 0.05). The expressions of Runx2 and Osterix in osteoblasts showed a significant increase among the control (C30 and C60) and treatment groups (T30 and T60) (p < 0.05). Conclusion: Umbilical cord mesenchymal stem cells improve bone regeneration in diabetic animal model with apical periodontitis, in terms of osteoblasts, Runx2 and Osterix.